Perceptions of the European Green Deal: Understanding Public Sentiment - Steve Borchardt; Matteo Trane; Stefano Cisternino; Luisa Marelli (Social Media + Society)
Launched in December 2019, the European Green Deal (EGD) represents the European Union’s (EU) ambitious policy framework to achieve climate neutrality by 2050. This study employs a sentiment analysis of 582,156 tweets from the beginning of 2020 to April 2024 to understand the evolution of public sentiment toward the EGD. Grounded in Social Representations Theory and Framing Theory, we analyze sentiment trends, topic distributions, and the impact of key policy and external events (e.g. COVID-19 spread) on public sentiment. The results reveal predominantly neutral sentiment (61.68%), with more positive (28.26%) than negative (10.06%) sentiment overall and a substantially stable trend over time. EU-affiliated accounts showed higher positive sentiment compared to non-EU-affiliated accounts. Sentiment trends were correlated with key policy announcements and global events, demonstrating the intricate relationship between policy communication and the formation of public opinion. The study identified key themes and specific initiatives driving positive sentiment, including those linked to the first EU climate law and climate targets, Farm to Fork, and New European Bauhaus. Conversely, economic concerns, challenges in policy implementation challenges, ecosystem conservation status, and food system, and energy security issues appeared as associated with negative sentiment. The findings highlight the importance of targeted communication strategies, transparent response to skepticism, communication of policy processes, and stakeholder feedback collection tool enhancement to leverage public sentiment in support of the EU green transition, paving the way for future research to explore regional nuances and sentiment monitoring.